Sustainable conversion of carbon dioxide into diverse hydrocarbon fuels via molten salt electrolysis - Al-Juboori, Ossama; Sher, Farooq; Rahman, Saba; Rasheed, Tahir; Chen, George Z. (American Chemical Society, 2020)
In recent decades, the unlimited use of fossil fuels mostly for power generation has emitted a huge amount of carbon dioxide in the atmosphere which in return has led to global warming. Here we use green technology, the molten salt electrochemical system comprising of titanium and mild steel as a cathode with graphite anode whereas molten carbonate (Li2CO3-Na2CO3-K2CO3; 43.5:31.5:25 mol%), hydroxide (LiOH-NaOH; 27; 73 and KOH-NaOH; 50:50 mol %) and chlorides (KCl-LiCl; 41-59 mol%) salts as electrolytes This study investigates the effect of temperature, feed gas ratio CO2/H2Oand use of different cathode materials on hydrocarbon product along with current efficiencies. Gas chromatography and mass spectroscopy have been applied to analyze the gas products. According to GC results, more specific results in terms of high molecular weight and long chain hydrocarbons were obtained by using titanium cathodic material rather than mild steel. The results revealed that among all the electrolytes, molten carbonates at 1.5V and 425˚C produced higher hydrocarbons as C7H16 while all other produced CH4. The optimum conditions for hydrocarbon formation and higher current efficiencies in case of molten carbonates were found to be 500oC under a molar ratio of CO2/H2O of 15.6. However, the current efficiencies do not change on increasing the temperature from 425 to 500oCand is maintained at 99% under a molar ratio of CO2/H2O of 15.6. The total current efficiency of the entire cathodic product reduced clearly from 95 to 79% by increasing the temperature under a CO2/H2O ratio of 9.2 due to the reduction of hydrocarbon generation in this case, despite the formation of C7H16. Therefore, due to its fast electrolytic conversion rate and low cost (no use of catalyst) the practice of molten salts could be an encouraging and promising technology for future investigation for hydrocarbon fuel formation.